Mектеп программалары ве дерсликлеринде бешинджи сыныф талебелерининъ къырымтатар тилинде диалогик нуткъы - Яяева, Н.М. (Культура народов Причерноморья, 2013)
Макъаледе бешинджи сыныф талебелерининъ тиль беджериклерини инкишаф эттирюв ве
мукеммеллештирюв меселеси айдынлатыла. Къырымтатар тили боюнджа программанынъ талили
косьтерильген. Къырымтатар тили дерслиги тедкъикъат мевзусы боюнджа талиль этиле.
Анахтар сёзлер: къырымтатар тилинде диалогик нуткъ, коммуникатив беджериклер, къаршылыкълы
мунасебет вазиети, программа ве дерсликнинъ мундериджеси. В статье рассматривается вопрос крымскотатарского языка как учебного предмета в
школе. Рассматривается речевая функция крымскотатарского языка. Дается анализ требований по
крымскотатарскому языку, заложенные в действующей программе для средней общеобразовательной
школы, а также описывается анализ учебника по крымскотатарскому языку для пятого класса.
Ключевые слова: крымскотатарская диалогическая речь, коммуникативные умения, ситуация общения,
содержание программы и учебника. У статті розглядається питання кримськотатарської мови як навчального предмета в
школі. Розглядається мовна функція кримськотатарської мови. Дається аналіз вимог з
кримськотатарської мови, закладені в чинній програмі для середньої загальноосвітньої школи, а також
описується аналіз підручника з кримськотатарської мови для п'ятого класу.
Ключові слова: кримськотатарська діалогічна мова, комунікативні вміння, ситуація спілкування, зміст
програми і підручника. The article deals with the problem of developing and improving the language skills of 5th form
students. It shows the analysis of program for the Crimean Tatar language at school. It describes the analysis of
the Crimean Tatar language textbook on the subject of the study, raises the issue of the Crimean Tatar language
as a subject in school, consider speech function of the Crimean Tatar language.
It observes requirements for the Crimean Tatar language inherent in the current program for secondary school
and describes the analysis of the Crimean Tatar language textbook for 5th form pupils.
The topic of research shows two main problems of the Crimean Tatar Language education. The analysis of
existing programs and the Crimean Tatar language 5th form textbook as well as mastering the skills of dialogue
speech in previous forms talk about the strengths and weaknesses of the study of the problem.
The actual content of the program in achieving the goal, what convinces monitor student speech.
The assimilation of material for the development of speech is going through the formation of practical language
skills as a result of an intuitive approach to their correct speech patterns, so each speech is achieved as a new or
intuitively combined with other similar tasks.
We consider, to insert the program to the list of language cues and dialogical unity, which are based on the
training-trained voice and speech exercises. Methodological manuals should describe the speech situations,
samples of dialogue speech.
Keywords: Crimean Tatar dialogical discourse, communicative skills, communicative situation, the content of
the program and textbook.